2019
DOI: 10.3390/bios9020052
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Generic Immunorecognition of Glycopeptide Antibiotics Promoted by Unique and Multiple Orientations of Hapten

Abstract: Conjugation chemistry does not always provide adequate spatial orientation of hapten in immunogens for the best presentation of generic or individual epitopes. In the present study, the influence of unique and multiple orientations of immunizing hapten on the immune response repertoire was compared to select generic recognition system. The glycopeptides, teicoplanin (TPL) and ristomycin (RSM), were conjugated to BSA to produce immunogens with unique and multiple orientations of haptens. Polyclonal antibodies g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The literature search on the competitive immunoassay of small analytes has shown that an effective way to shift the cross-reactivity profile towards the desired cross-reactant is to use the latter as a coating or a labeled hapten. The phenomenon of immunorecognition enhancement was clearly observed with such analytes as spiramycin, vancomycin [27], and teicoplanin [28]. As can be seen from Figure 2, five coating conjugates were prepared.…”
Section: Preparation Of Conjugated Antigensmentioning
confidence: 94%
“…The literature search on the competitive immunoassay of small analytes has shown that an effective way to shift the cross-reactivity profile towards the desired cross-reactant is to use the latter as a coating or a labeled hapten. The phenomenon of immunorecognition enhancement was clearly observed with such analytes as spiramycin, vancomycin [27], and teicoplanin [28]. As can be seen from Figure 2, five coating conjugates were prepared.…”
Section: Preparation Of Conjugated Antigensmentioning
confidence: 94%
“…They are often aggravated by the low immunogenicity or non-uniqueness of the selected structures and, moreover, require complex preliminary chemical synthetic work. An alternative approach to competitive immunoassays is to use different antigen derivatives in immunization and analysis [19][20][21][22][23][24][25][26][27][28]. This so-called "heterologous" immunoassay ensures that not all antibodies produced are involved in the competitive analytical interactions, and the spectrum of selectivity is thereby narrowed in comparison with the traditional "homologous" assay.…”
Section: Introductionmentioning
confidence: 99%